2013
DOI: 10.4028/www.scientific.net/amr.690-693.1418
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on Tautomerization Mechanism of 6-Thioguanine

Abstract: The tautomerization reaction mechanisms between three stable 6-thioguanine tautomers were investigated theoretically using B3LYP/6-311+G(d,p) method. The results show that the pathway P(1) is to isomerize from TG(9,10,10,11) to TG(1,9,10,10) and the needed activation Gibbs free energy barrier is 112.7 kJ/mol with the rate constant of 1.12×10-7 s-1. Another two pathways P(2) and P(3) are to isomerize from TG(1,9,10,10) to TG(1,7,10,10) and the activation Gibbs free energy barriers of the rate-determining steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This desflurane radical mainly comes from the result of H abstraction reaction in desflurane molecule via a Cl atom [7] or OH radical [12] attacking, which was demonstrated in the former report. After the attacking of one O 2 molecule, it is found that a CF 3 C(O 2 )FOCHF 2 radical was generated through one oxygen molecular addition and this process includes two reaction steps, which are following as…”
Section: Reaction 1: the Complex P1 Generation Via An Oxygen Moleculementioning
confidence: 78%
See 1 more Smart Citation
“…This desflurane radical mainly comes from the result of H abstraction reaction in desflurane molecule via a Cl atom [7] or OH radical [12] attacking, which was demonstrated in the former report. After the attacking of one O 2 molecule, it is found that a CF 3 C(O 2 )FOCHF 2 radical was generated through one oxygen molecular addition and this process includes two reaction steps, which are following as…”
Section: Reaction 1: the Complex P1 Generation Via An Oxygen Moleculementioning
confidence: 78%
“…It has been demonstrated that the B3LYP functional is able to provide reliable geometrical structures, zero point energies (ZPE), and frequencies for stationary points on the potential energy surface (PES) for organic reactions with a relatively high computational efficiency [8][9][10][11][12][13][14][15][16][17][18]. Hence, both density functional theory method B3LYP and configuration interaction QCISD(T) (quadratic with singles doubles and perturbative inclusion of triples) method [19] were employed for investigating the degradation reaction mechanisms between desflurane radical and oxygen molecule in the presence of NO.…”
Section: Computational Detailsmentioning
confidence: 99%